Performance of lightweight concrete using palm oil clinker aggregates for precast application - Azillah, Nazry (2018)
Palm oil clinker (POC) is a waste from the incineration process of palm oil shell and palm oil fibre which can be easily obtained from palm oil mill. This study focused on the 100% replacement of fine and coarse POC aggregates in concrete. The utilization of POC has been accepted by researcher to produce lightweight concrete and has good potential to replace natural aggregates. In this study, the characterization of fine and coarse aggregates consist of the physical and mechanical properties. Specific gravity, water absorption, dry loose bulk density, moisture content, sieve analysis, fineness modulus and Los Angeles abrasion tests were conducted to evaluate the physical properties. While for the mechanical properties of aggregate, tests on aggregate crushing value and aggregate impact value were carried out. It was found that the coarse and fine POC aggregates produce a density of 817.17 kg/m3 and 917.82 kg/m3, respectively, which were lighter than normal granite and sand as much as 36.85% and 29.45%. This is due to the porous nature of POC aggregates. POC absorbs excessive water which contributes to higher water absorption of 15.17% and 5.35% for fine and coarse, respectively. The sieve analysis result shows that fine and coarse POC comply with American Society for Testing and Materials (ASTM) C330/330M (2014), thus indicates that fine and coarse POC aggregates can be considered as a well-graded aggregate. A concrete mixture consists of 100% fine and coarse POC aggregates were then designed according to American Concrete Institute (ACI) 211.2 (1998), producing lightweight concrete with a density of 1990.33 kg/m3. The normal weight concrete (NC) and lightweight concrete or later known as palm oil clinker concrete (POCC) were tested for its fresh and hardened properties. Slump test was performed to assess its workability while for the hardened concrete tests, density, water absorption, ultrasonic pulse velocity, compressive strength, tensile splitting, flexural strength, modulus of elasticity and Poisson’s ratio tests were conducted. To evaluate suitability in the structural precast application, normal concrete wall (NCW) and lightweight precast wall (LPW) panels were constructed and tested under static loading. LPW panel exhibited lower axial load capacity by 44.13% from NCW and this is mainly due to the lower initial stiffness. Moreover, the higher Poisson’s ratio value for POCC reflects the higher lateral displacement recorded by LPW at peak load which was 4.46 mm compared to only 1.1 mm for NCW. The failure mode and cracking pattern for both panels were similar except LPW exhibited concrete spalling during failure. The utilization of POC aggregate shows significant impact as LPW had larger strain at lower load. From the study conducted, POCC with air voids in the concrete contributes to lower initial stiffness of LPW. In conclusion, the LPW is suitable to be used as low load structural members.